Analysis of the Feasibility of a Local Wisdom-Based Physics Learning Module Using Rabi Ro’o Games Integrated with the Merdeka Curriculum on Newton's Laws of Motion - Erlangga, Sony Yunior; Septiani, Devi; Rohmat, Ali; Fitriyah, Isnanik Juni (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2023)
This research evaluates a Physics Pedagogy based on Project-Based Learning (PjBL) integrated with the Merdeka Curriculum for Newton's Laws of Motion material in Grade X high school. The method used is Research and Development (RnD) with a 5D model, focusing up to the Develop stage. Define includes needs analysis and student competency identification, while Design involves the creation of modules and student worksheets. The Develop stage includes development, expert validation, and limited testing. The results indicate a high feasibility of the local wisdom-based module using Rabi Ro’o games integrated with the Merdeka Curriculum, as assessed by experts in terms of content, teaching, and language aspects. Positive student responses confirm that this module is suitable for high school Physics instruction.